Promoting creativity: the role of proactive vitality management and playful work design - Noor Shabrina Hidayat; Endang Parahyanti (HUMANITAS published by Universitas Ahmad Dahlan., 2026)
Grounded in the Job Demands–Resources (JD-R) theory, this study examines the role of proactive strategies in enhancing employee creativity. According to the Indonesian Employment Outlook 2024 report, amid increasing workforce demands driven by technological advancement, creativity, initiative, and originality have become essential competencies. This study investigates the relationship between Proactive Vitality Management (PVM), Playful Work Design (PWD), and Creative Work Performance (CWP). A survey was conducted with 329 Indonesian workers, and the data were analyzed using Hayes’ PROCESS Model 4. The results indicate that PVM has a significant positive effect on CWP both directly and indirectly through PWD as a mediator. PVM enables individuals to maintain physical and mental energy, while PWD reflects individuals’ proactive efforts to create more enjoyable and challenging work experiences that foster creativity. Hypothesis testing showed that PVM significantly affects CWP (B=1.269, p<0.001), with PWD partially mediating this relationship (B=0.56, p<0.001). These findings highlight the importance of proactive personal strategies in promoting creative work performance. Organizations are encouraged to support employees in managing their energy and engaging in proactive work design. Future research may explore potential boundary conditions influencing these relationships.